The picturesque prison : Evelyn Waugh and his writing - Heath, Jeffrey M. (CEL - Canadian Publishers Collection., 1982)
This study of the life and works of Evelyn Waugh traces the novelist's pursuit of his vocation and his long retreat from a world which he came to regard as a spiritual dungeon. Jeffrey Heath explores the paradoxical elements in Waugh's career: his quest for a refuge itself proved to be a prison and his devotion to the Augustan graces was accompanied by a lasting attraction to a Dionysiac age without restratint. The deep cleft in Waugh's nature imbued his art with the characteristic quirky complexity which has fascinated many readers, but it left him a choleric and melancholy man who never fully accepted his calling as a writer.